A case of immune checkpoint inhibitor-related conjunctivitis controlled by tacrolimus eye drops - Ayaka Kawaguchi; Hayato Tanaka; Hitoshi Tabuchi; Kei Nakai; Atsuki Fukushima (American Journal of Ophthalmology Case Reports)
Purpose: We report a case where tacrolimus eye drops may have alleviated immune checkpoint inhibitor (ICI)-related conjunctivitis attributed to nivolumab. Observations: A 61-year-old female complained of conjunctival hyperemia and eyelid swelling in both eyes. The patient was previously undergoing treatment for gastric cancer with nivolumab, with the final dose administered one week before the first ophthalmology visit. Initially, the patient was diagnosed with allergic conjunctivitis, managed with 0.1 % fluorometholone eye drops, 4 times daily in both eyes, but the symptoms did not improve despite 27 weeks of treatment, ICI-related conjunctivitis was considered, and the patient was prescribed with, 0.1 % tacrolimus eye drops twice daily in both eyes. One week later, there was a remarkable improvement in the conjunctival symptoms. Three months after, the conjunctival hyperemia reduced and swelling disappeared in both eyes, and, the frequency of instillation was reduced to once daily. The condition remains in remission with 0.1 % tacrolimus eye drops applied once daily in both eyes. Conclusions: Tacrolimus eye drops may have played a role to suppress ICI-related conjunctivitis.